LEGAL ANALYSIS ON AMDAL AS AN ENVIRONMENTAL PROTECTION DOCUMENT - Trias Hernanda (Legal Standing : Jurnal Ilmu Hukum, 2020)
Amdal is an analysis of environmental impacts. The purpose of Amdal is to analyze aneffect that arises from a planned construction project or building. The Amdal documentis mandatory for any initiator or entrepreneur who will apply for an environmentalpermit. This obligation is because it aims to protect the environment from damagecaused by development. However, many entrepreneurs do not understand the existenceof an Amdal, so they mostly build first and then take care of it. Amdal. The researchmethod used in this research is juridical normative or doctrinal. The traditionalmaterials used are primary and secondary legal materials; primary standard materialsinclude statutory regulations and legal documents. Based on the regular analysis fromthe author, the Amdal document has a critical position to maintain the quality of theenvironment and the sustainability of public health. On the other hand, Amdal alsoguarantees sustainable development and environmentally sound development (ecodevelopment).